Inverse vulcanization of sulfur with vinylic POSS. (2nd November 2019) - Anyszka, Rafał; Kozanecki, Marcin; Czaderna, Anna; Olejniczak, Magdalena; Sielski, Jan; Siciński, Mariusz; Imiela, Mateusz; Wręczycki, Jakub; Pietrzak, Dominik; Gozdek, Tomasz; Okraska, Michał; Szynkowska, Małgorzata I.; et al.
ABSTRACT: Novel sulfur-silsesquioxane random copolymer (poly(S-r-POSS)) was synthesized via the radical reaction between liquid sulfur and octavinyl silsesquioxane. Particulate solid POSS was dispersed in molten sulfur and heated in order to initiate the free radical reaction (inverse vulcanization). The appearance of new C–S bonds along with the disappearance of C=C bonds from vinyl groups was confirmed by Raman and FTIR spectroscopy. Moreover, the formation of saturated single C–C bonds from the reacting vinyl groups was revealed by FTIR. Microhomogenity of the copolymer was analyzed by means of SEM-EDS mapping and its thermal properties were studied using the TG-DSC method. After the extraction of free unreacted sulfur and POSS the copolymer exhibits porous micromorphology promising for application in lithium–sulfur batteries or heavy metals ion capturing. Highlights Synthesis of silsesquioxane-sulfur hybrid copolymer via inversed vulcanization Highly porous cross-linked morphology Potential utilization for lithium–sulfur batteries or heavy metals ion capturing GRAPHICAL ABSTRACT: